2004
DOI: 10.1023/b:neon.0000024242.59770.7a
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial Infusion of Carmustine in the Rat Brain Stem with Systemic Administration of O-benzylguanine

Abstract: Interstitial infusion of carmustine (BCNU) into the rat brain stem in conjunction with systemic administration of O6-benzylguanine (O6-BG) was performed in an effort to assess clinical tolerance. A total of 12 rats underwent stereotactic cannula placement into the pontine segment of the brain stem. Six of the rats underwent a 24-h infusion of BCNU (Volume of infusion [Vi] 200 microl) at its maximal concentrated dose (3.3 mg/ml) in 5% dextrose water. Six additional rats underwent 24-h infusion of BCNU preceded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…One possible candidate is bevacizumab, as it has already been used for systemic therapy studies in glioma patients with promising results [27]. Another option is the combination of temozolomide with resistance modifiers such as O6-benzyl-guanine, INF-beta, and MGMTsiRNA [15,19,21,23].…”
Section: Discussionmentioning
confidence: 99%
“…One possible candidate is bevacizumab, as it has already been used for systemic therapy studies in glioma patients with promising results [27]. Another option is the combination of temozolomide with resistance modifiers such as O6-benzyl-guanine, INF-beta, and MGMTsiRNA [15,19,21,23].…”
Section: Discussionmentioning
confidence: 99%
“…20 Furthermore, studies have shown that local perfusion of the rat brainstem with chemotherapeutic agents, such as BCNU, carboplatin, and gemcitabine, is safe. 25,103 Distribution studies with CED have demonstrated that carboplatin can reach therapeutic levels in the brainstem, although it was shown that the drug diffused up to 4 mm around the tip of the cannula. Thus, larger tumors may need the placement of more than 1 cannula.…”
Section: New Therapeutic Perspective Strategiesmentioning
confidence: 99%
“…The surgical procedure is performed as previously described (8, 17, 21). The animal is anesthetized by inhalational isoflurane and placed in a stereotactic frame (Kopf Instruments, California).…”
Section: Methodsmentioning
confidence: 99%